Efektivitas Perlindungan Hukum Terhadap Saksi Pelapor dalam Menanganani Pelanggaran Pemilu - Cantika, Trielvani Margaretha; Sinaga, Budiman (Innovative: Journal Of Social Science Research, 2025)
The government is responsible for providing legal protection as part of the service to ensure that every citizen feels safe. In order to guarantee legal certainty in reporting election violations, the government needs to provide legal protection. This is in line with Article 1 Paragraph 2 of the 1945 Constitution of the Republic of Indonesia which states that sovereignty lies in the hands of the people, so that their constitutional rights must be respected and upheld by the state. The implementation of elections is often accompanied by various forms of violations. To overcome this problem, Law No. 13 of 2006 concerning Protection of Witnesses and Victims was issued. As a further step, the government established the Witness and Victim Protection Agency (LPSK) to provide protection and assistance to witnesses and victims. In cases of election crimes, LPSK plays a role in protecting witnesses, where witnesses can apply for protection in accordance with applicable procedures. LPSK is responsible for ensuring protection that includes the rights and obligations of witnesses in the process of resolving violations. This protection is provided through two approaches, namely a combination of the procedural rights model and the service model.